Reconceptualizing of Bank Liability for Customer Losses Resulting from Social Engineering Through the Doctrine of Strict Liability and the Reversal of the Burden of Proof Based on the Cheapest Cost Avoider Principle to Ensure Equality of Arms - Rizkya Wina Yahriza Pohan; Zahra Arya Zaura; Louis Venansius; Arsyah Wijaya; Muhammad Fauzi Rais Lutfi (Universitas Negeri Semarang, 2026)
The rapid digitalization of banking services in Indonesia has generated a significant surge in social engineering fraud, with 99 percent of banking fraud cases attributable to psychological manipulation. This study aims to reconceptualize bank liability for customer losses arising from social engineering-based OTP fraud and to reconstruct the burden of proof mechanism in civil procedural law to guarantee equality of arms. This research employs a normative legal methodology with a qualitative approach, utilizing statutory, conceptual, and case analysis perspectives. Primary legal materials include relevant legislation and financial authority regulations, while secondary materials consist of legal doctrine, academic journals, and prior scholarly works. The findings reveal two principal conclusions. First, transactions resulting from social engineering contain Wilsgebreken under Article 1321 of the Civil Code, as customer authorization is obtained through psychological manipulation rather than free will. Reconceptualizing bank liability under strict liability is justified through the Cheapest Cost Avoider doctrine, which allocates responsibility to banks as the most efficient party to prevent losses, and through fiduciary duty, which obliges banks to actively protect customers from predictable digital risks. Second, conventional proof mechanisms based on Actori Incumbit Probatio violate equality of arms, as all forensic evidence is held exclusively by banks. A three-tier burden-shifting mechanism is proposed: customers establish a Prima Facie threshold, the burden shifts to banks to prove system integrity and compliance with duty of care, and courts conduct substantive material truth examination. Regulatory harmonization across the Financial Services Authority, Bank Indonesia, and the judiciary is essential for effective implementation.